1996
DOI: 10.1074/jbc.271.13.7752
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Consensus Cyclin-dependent Kinase Phosphorylation Site Unique to the Nuclear Form of Human Deoxyuridine Triphosphate Nucleotidohydrolase

Abstract: , we identified two distinct isoforms of dUTPase in human cells. These isoforms are individually targeted to the nucleus (DUT-N) and mitochondria (DUT-M). The proteins are nearly identical, differing only in a short region of their amino termini. Despite the structural differences between these proteins, they retain identical affinities for dUTP (preceding article). In previous work, this laboratory demonstrated that dUTPase is posttranslationally phosphorylated on serine residue(s) (Lirette, R., and Caradonna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…It is possible that the mitochondrial location of TS is due to the nonspecific adherence of TS to the surface of the mitochondria, but the extensive washing procedure employed would appear to mitigate against this possibility, as well as our recent finding that the enzyme can be released on hypotonic lysis of the mitochondria. 3 Preliminary results reveal that the H35 TS is labeled on a serine, as has been found also for dUTPase (33). Because of these common properties of TS and dUTPase, it would not be unreasonable to assume that the two enzymes reside in the same regions of the cell, possibly in the proposed replitase complex (12).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It is possible that the mitochondrial location of TS is due to the nonspecific adherence of TS to the surface of the mitochondria, but the extensive washing procedure employed would appear to mitigate against this possibility, as well as our recent finding that the enzyme can be released on hypotonic lysis of the mitochondria. 3 Preliminary results reveal that the H35 TS is labeled on a serine, as has been found also for dUTPase (33). Because of these common properties of TS and dUTPase, it would not be unreasonable to assume that the two enzymes reside in the same regions of the cell, possibly in the proposed replitase complex (12).…”
Section: Discussionmentioning
confidence: 59%
“…Alternatively, the enzyme might be chaperoned into the nucleus by a protein similar to that described recently for the Id family of helix-loop-helix proteins (32). It is of interest to note that dUTPase, like TS, although associated with the nucleus, does not contain a characteristic nuclear localization signal either (15,33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To determine the structural differences between these isoforms, a combination of NH 2 -terminal protein sequencing and mass spectrometry was utilized to characterize each form in detail, demonstrating that the two isoforms are largely identical, differing only in a short region of their amino termini. Analysis of dUTPase phosphorylation demonstrated that DUT-N is serinephosphorylated at a consensus cyclin-dependent protein kinase phosphorylation site (Ser 11 of DUT-N), suggesting a link to cell cycle regulation (15). While DUT-M contains the identical site, it does not undergo phosphorylation in HeLa cells.…”
mentioning
confidence: 99%
“…While DUT-M contains the identical site, it does not undergo phosphorylation in HeLa cells. Site-directed mutagenesis analysis demonstrates that serine phosphorylation of DUT-N does not regulate enzymatic activity, and the biological significance of DUT-N phosphorylation remains unclear (15). Kinetic analysis of each isoform demonstrates that they retain identical affinities for dUTP despite their structural differences.…”
mentioning
confidence: 99%